INTEGRASI PEMBELAJARAN PAI PENDEKATAN MULTIDISIPLINER DI PERGURUAN TINGGI UMUM - Yudhi Fachrudin (Institut Binamadani Indonesia, 2026)
This study aims to analyze the concept of integrating Islamic Religious Education (IRE) into the curriculum using a multidisciplinary approach at public universities, identify forms of integration within course materials, and formulate practical implications for teaching. The method used is qualitative research in the form of library research through descriptive-analytical analysis of various relevant scientific literature sources. The results of the study indicate that a multidisciplinary approach is capable of integrating Islamic teachings with various academic disciplines such as sociology, psychology, anthropology, and the natural sciences, thereby resulting in a more holistic, contextual, and practical learning experience. This integration is realized in the form of teaching materials that link Islamic values with social realities and is supported by innovative learning strategies such as problem-based learning and project-based learning. This study concludes that the integration of Islamic Education (PAI) learning based on a multidisciplinary approach is capable of producing holistic, contextual, and practical learning in shaping students’ character and competencies relevant to the demands of the times.